Slayed - Marrone, Amanda (Simon Pulse, 2010)
Daphne Van Helsing hates being a vampire slayer. Her parents' latest job is in Maine, where they are forced to work with the Harkers, a rival slayer family. The Harkers' son Tyler is crush-worthy but he's Daphne's sworn enemy. When something truly evil comes to the town, what changes must occur to overcome the evil?